Efficacy and safety of compound amino acid capsules in the treatment of malnutrition and calcium and phosphorus metabolism disorders in maintenance hemodialysis patients - WU Wangshu; WANG Minzhou; SONG Ahui; ZHAO Bingru; LU Jiayue; HONG Wenkai; GU Leyi; XIE Kewei; LU Renhua (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the efficacy and safety of compound amino acid capsules in the treatment of malnutrition and calcium and phosphorus metabolism disorders in maintenance hemodialysis patients. Methods·In this prospective, randomized, controlled, single-center study, forty maintenance hemodialysis patients from Renji Hospital, Shanghai Jiao Tong University School of Medicine were randomly divided into two groups, the treatment group (n=21) and the control group (n=19). The treatment group was given oral compound amino acid capsules on the basis of regular hemodialysis treatment, while the control group received no special nutritional intervention. Serum albumin, prealbumin, hemoglobin, ferritin, calcium, phosphorus, 1,25-(OH)2-D3 and intact parathyroid hormone levels were analyzed every 3 months, and the incidence of adverse events including death, cardio-cerebrovascular accidents and vascular access failure was recorded. The total follow-up period was 9 months. Results·Serum albumin and prealbumin in the treatment group at 6-month and 9-month were significantly higher than the baseline parameters (albumin, t=3.574, 5.599, both P<0.05; prealbumin, t/Z=-2.485, 2.921, both P<0.05). Albumin in the control group increased at 9-month with a lower amplification compared to the treatment group (t=3.877, P=0.001), while the difference of prealbumin showed no statistical significance during follow-up. Hemoglobin and serum ferritin in the treatment group started to increase at 3-month (hemoglobin, t=2.192; ferritin, t=2.994; both P<0.05). Phosphorus in treatment group decreased at 3-month and 9-month (t/Z=-2.743, -2.103, both P<0.05), while phosphorus in the control group remained relatively stable during the first 6 months and increased at 9-month (Z=-2.178, P=0.029). Calcium and 1,25-(OH)2-D3 in the treatment group at 3-month and 6-month were significantly higher than the baseline parameters (calcium, t=4.581, 4.922, both P=0.000; 1,25-(OH)2-D3t/Z=4.504, -2.374, both P<0.05), while the increase in blood calcium in the control group was significantly smaller than that in the treatment group during the same period. 1,25-(OH)2-D3 in the control group showed no significant improvement. There was no significant difference in intact parathyroid hormone level, incidence of adverse events and other laboratory examination results between the two groups. Conclusion·Compound amino acid capsules can ameliorate the nutrition status and regulate calcium and phosphorus metabolism effectively and safely in maintenance hemodialysis patients.